The difficulty in defining the true high-risk smoldering myeloma - Weinhold, Niels; Rasche, Leo (Clinical cancer research, 2024)
Early intervention trials have been initiated for the precursor disease smoldering myeloma (SMM). A recent study showed that genomic complexity varies widely among patients treated for high-risk SMM and is associated with response to triplet therapy, suggesting that established clinical risk scores often fail to discriminate between stable and aggressive disease.See related article by Kazandjian et al., p. 4482